2003
DOI: 10.1074/jbc.m309548200
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Expression of GPEET Procyclin and Its Membrane-associated Kinase in Trypanosoma brucei Procyclic Forms

Abstract: GPEET procyclin is a major glycosylphosphatidylinositol-anchored protein of procyclic (insect stage) trypanosomes in culture and is heavily phosphorylated in the GPEET pentapeptide repeat. The phosphorylation reaction is a late event and occurs during maturation and transport of GPEET or on the parasite surface by an ecto-protein kinase. Initial biochemical characterization of the GPEET kinase activity now shows that it depends on bivalent cations for maximal activity, is stimulated by sulfhydryl group reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…We have found that a mutant that constitutively expresses GPEET is transmitted very efficiently (unpublished data). The GPEET expressed by late procyclic forms and epimastigote forms was not phosphorylated, however, which is consistent with reports that the activity of the kinase is restricted to early procyclic forms [29].…”
Section: Discussionsupporting
confidence: 91%
“…We have found that a mutant that constitutively expresses GPEET is transmitted very efficiently (unpublished data). The GPEET expressed by late procyclic forms and epimastigote forms was not phosphorylated, however, which is consistent with reports that the activity of the kinase is restricted to early procyclic forms [29].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, there might also be post-translational modifications or non-peptide moieties that are stage-specific. For example, the activity of the kinase that phosphorylates GPEET is restricted to early procyclic forms [33]. It is also known that early procyclic forms of T. congolense preferentially express PRS, a protease-resistant surface glycoconjugate [34], [35], although an equivalent molecule has not been reported for T. brucei .…”
Section: Discussionmentioning
confidence: 99%
“…By 24 h, the cells show the characteristic profile of early procyclic forms, with high levels of GPEET and traces of EP. GPEET is phosphorylated by a membrane-associated kinase [13] that also becomes active within a few hours of triggering differentiation [3,11,14]. If glycerol is present in the medium [3] and the mitochondrial alternative oxidase is active [15], the cells continue to proliferate as early forms and express GPEET.…”
Section: Introductionmentioning
confidence: 99%
“…If glycerol is present in the medium [3] and the mitochondrial alternative oxidase is active [15], the cells continue to proliferate as early forms and express GPEET. In medium lacking glycerol, the trypanosomes differentiate to late procyclic forms within 7–9 d; this is marked by the replacement of GPEET by the glycosylated isoforms of EP (EP1 and EP3) [11] and loss of GPEET kinase activity [13]. The same sequence of events, expression of GPEET by early procyclic forms and its replacement by EP1 and/or EP3 in established procyclic forms also occurs during tsetse fly infections [12].…”
Section: Introductionmentioning
confidence: 99%